2014
DOI: 10.1094/cchem-05-13-0096-r
|View full text |Cite
|
Sign up to set email alerts
|

Aroma Stability of Millet Powder During Storage and Effects of Cooking Methods and Antioxidant Treatment

Abstract: Cereal Chem. 91(3):262-269Foxtail millet is a cereal crop that contains high levels of unsaturated fatty acids, so that processed food such as instant millet powder is susceptible to lipid oxidation, which gradually leads to deteriorated flavor and quality. In this work, volatiles of millet powder samples with or without storage at room temperature for 12 months were extracted and analyzed by gas chromatography-olfactometry/mass spectrometry. In fresh steamed millet powder, hexanal, 2-pentylfuran, and 3-octen-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“…The results, which showed aldehydes to be the most numerous foxtail millet volatiles, were similar to those of two prior studies (Liu et al 2012;Wang et al 2014). Aldehydes (62.88-81.6%) were the predominant volatile components in various cultivars, followed by noncategorized compounds (6.63-15.26%), hydrocarbons (4.33-11.59%), ketones (3.07-6.56%), alcohols (1.06-6.73%), and benzene derivatives (1.14-3.92%).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The results, which showed aldehydes to be the most numerous foxtail millet volatiles, were similar to those of two prior studies (Liu et al 2012;Wang et al 2014). Aldehydes (62.88-81.6%) were the predominant volatile components in various cultivars, followed by noncategorized compounds (6.63-15.26%), hydrocarbons (4.33-11.59%), ketones (3.07-6.56%), alcohols (1.06-6.73%), and benzene derivatives (1.14-3.92%).…”
Section: Resultssupporting
confidence: 89%
“…The compounds responsible for flavor travel to the nose during consumption and stimulate the olfactory receptors in the nasal cavity (Linforth and Taylor 1993). According to Wang et al (2014), ascorbyl palmitate can be added to millet powder as an antioxidant, and this significantly inhibits production of unpleasant odorants during storage. Studies have shown that aldehydes, alcohols, ketones, benzene derivatives, hydrocarbons, and acids are the volatile compounds of foxtail millet.…”
mentioning
confidence: 99%
“…Generally, the loss in activity was severe at temperature above 30°C since high temperature initiates unfolding processes that damage the active site. Lesser activity at low temperature might be attributed to decreased substrate or product diffusion rate (Wang et al 2014). The present study results are in accordance with the earlier reports on LOX purified from pearl millet seedlings (Babitha et al 2004) and rice (Ratachatachaiyos and Theerakulkait, 2009) who reported 25°C an optimum temperature for activity of enzymes.…”
Section: Molecular Massmentioning
confidence: 99%
“…and cause alteration of colour and organoleptic properties (Siedow 1991;Li et al 2007;Zilic et al 2010). LOX has been found responsible for the generation of off-flavour due to its action on PUFA, especially on linoleic and linolenic acid, resulting in deterioration of flavour and quality (Dahuja and Madaan 2004;Wang et al 2014;Mandal et al 2014;Chen et al 2016). Pearl millet has the high activity of LOX, therefore, the present study was carried out to evaluate its physico-chemical and kinetic properties, which could help in understanding its role in foul smell generation vis-a-vis shelf life of flour.…”
Section: Introductionmentioning
confidence: 99%
“…It is the oxidation product of linolenic acid and induces the production of the jasmonic acid involved in defense against pathogens infection . 3‐Octen‐2‐one was reported to be dominant in fresh steamed millet flour and has a rosy/fruity odour. It was absent in porridge of 8 varieties but higher in Q125 compared to the others ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%